Practices of Social Work with Migrants in Russia: Expert Assessments - E. A. Kovtun; V. P. Miletskiy (Дискурс, 2021)
Introduction. Regulation of social adaptation of migrants is one of the most important issues of state migration and social policy. One of the problems in the process of adaptation of migrants is the lack of a systematic approach to solving the problems faced by migrants in the host society. Therefore, it is necessary to study social work practices with migrants and their families to identify the most effective ones. The analysis of social work with migrants in state institutions of culture and social protection and in non-profit organizations reveals the situation with social work with migrants in Russia and identifies problems in the process of adaptation and integration of migrants into Russian society.Methodology and sources. Data for the sociological study in the form of expert interviews were collected using a qualitative method for evaluating social work practices with migrants. Semi-structured interviews were conducted in 2018–2019 in St Petersburg, Moscow, and Kazan with employees of professional centers for work with migrants, scientists specializing in the study of migration processes in their various aspects, and organizers of regular events (seminars, conferences) on this topic. The sample (30 experts) was formed by the snowball method. The number of expert interviews allowed us to cover a variety of social work practices both in government structures and in nonprofit organizations.Results and discussion. The results of the study showed that various practices are used in social work with migrants in Russia. A distinctive feature of these practices is the dominant focus on socio-cultural adaptation and integration. The effectiveness of social work practices with migrants and their families can be defined in specific changes: improving awareness and legal literacy of foreign citizens, increasing their legal protection, simplifying access to health and education services, accessibility of assistance in finding housing and employment, the possibility of improving professional skills and knowledge of the language, culture, and history of Russian society.Conclusion. Expert assessments revealed the most effective practices of social work with migrants used in Russia: legal advice, orientation courses, mobile counseling points where migrants can get advice from a social worker, a lawyer, and a doctor, and mobile applications integrated with state and non-state organizations. The results obtained show that the role of non-profit organizations (national cultural organizations for the preservation and development of cultures, the House of Friendship of Peoples) that use social practices to help migrants and their families adapt more effectively to the conditions of the host society is growing.